Aufnahme eines persönlich haftenden Gesellschafters bei einer GmbH & Co. KG zur Vermeidung der Offenlegung des Jahresabschlusses nach HGB - Devrimi Kaya (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Rechnungswesen und Prüfungswesen, 2010)
The paper analyses a strategy for avoiding the disclosure of the financial statements of a limited partnership with a limited liability company as general partner (GmbH & Co. KG) according to German Commercial Code (HGB). It describes the formal process of the joining of a natural person as an additional general partner to a 'GmbH & Co. KG' and gives recommendations how to arrange the legal position of this partner in the partnership agreement effectively.
Keywords: G18; G38; K22; M41; M42; 650; EHUG; Offenlegungsstrategien; GmbH &Co. KG; Vollhafterlösung; Gesellschaftsrecht; EHUG; disclosure strategies; limited partnership with a limited liability company as general partner; corporate law